Hollow (a novel), and, 'I do not think it is the end quite yet': The Uncanny Return of the Past - van Kesteren, Amy (2021)
Hollow is a story of loss and the uncanny reappearance of the dead. It begins when Isabelle, the novel’s narrator, encounters the ghost of Freddie, a boy she met when she was fourteen years old. Now, at the age of twenty-four, Isabelle recalls the summer she knew Freddie, spending days with him at the staithe beside the river in the small market town where she lived with her mother. Shifting back to the early days of their friendship, it becomes clear that Isabelle’s mother – along with the older generation of the town - disapprove of Freddie and his young mother. What also becomes clear, in the movements between past and present tense, is the haunting nature of memory, as brief glimpses of Isabelle’s adult life suggest that something terrible will happen to Freddie.